GG-35: A high yielding Spanish bunch groundnut, Arachis hypogaea L. variety for Gujarat State: GG-35: A high yielding Spanish bunch groundnut, Arachis hypogaea L. variety for Gujarat State - N D DHOLARIYA; G K SAPARA; C J RAJANI; R B MADARIYA (Journal of Oilseeds Research, 2023)
A Spanish bunch groundnut genotype GG 35 was developed on the basis of mean pod yield from the state level trials. It has recorded the highest pod yield of 3177 kg/ha as compared to the checks viz., GG 7 (2452 kg/ha), GJG 9 (2471 kg/ha) and TG 37A (2758 kg/ha). GG 35 had recorded average 100 kernel weight of 42.79 g, average 100 pod weight of 101.93 g and average shelling out-turn of 71.36%. The reaction against tikka, rust, stem rot and collar rot, the variety was comparable to the check varieties under field conditions whereas, the damages due to thrips was not observed in the released variety as well as check varieties. Based on the superior performance, GG 35 has been released for general cultivation in the kharif bunch groundnut growing areas of Gujarat state.